Attachment-Based Islamic Pedagogy: A Relational Framework for Emotional Regulation and Life Skills Development among Autistic Students in Pesantren - Nurul Azizah; Ummu Jauharin Farda; Jihan Avie Yusrina; Erna Dwi Nugraini; Linda Indiyarti Putri (Jurnal Pendidikan Islam, 2026)
Despite the growing emphasis on inclusive education, limited attention has been given to how attachment-based relationships within pesantren (Islamic boarding schools) support the emotional and adaptive development of autistic learners. This study explores how attachment-based caregiving contributes to emotional regulation and life skills development among students with Autism Spectrum Disorder (ASD) at pesantren in Indonesia. To achieve this, the research employed a qualitative case study design, and data were collected through in-depth interviews, participant observation, and document analysis involving ten autistic students, five caregivers, and the boarding school supervisor. Data credibility was ensured through source and method triangulation, and thematic analysis supported by Quirkos software was used to analyze the data. The findings reveal that secure attachment, characterized by caregivers’ responsiveness, affection, and consistency, serves as a secure base and safe haven that facilitates emotional regulation and adaptive social behaviors. Furthermore, structured religious and communal activities further promote important life skills, including self-awareness, empathy, critical thinking, problem-solving, and leadership. Based on these insights, the study proposes Attachment-Based Islamic Pedagogy (ABIP) as a relational framework that integrates secure attachment with the core values of ta’dīb and tarbiyah bi al-raḥmah. Collectively, these findings highlight the significant potential of faith-based residential education to strengthen inclusive Islamic educational practices and better support children with special needs.